Implementing Algorithm‐Guided Warfarin Dosing in an Ethnically Diverse Patient Population Using Electronic Health Records and Preemptive CYP2C9 and VKORC1 Genetic Testing. Issue 5 (18th August 2016) - Obeng, A Owusu; Kaszemacher, T; Abul‐Husn, NS; Gottesman, O; Vega, A; Waite, E; Myers, K; Cho, J; Bottinger, EP; Ellis, SB; Scott, SA
Abstract : Implementation of pharmacogenetic‐guided warfarin dosing has been hindered by inconsistent results from reported clinical trials and a lack of available algorithms that include alleles prevalent in non‐white populations. However, current evidence indicates that algorithm‐guided dosing is more accurate than empirical dosing. To facilitate multiethnic algorithm‐guided warfarin dosing using preemptive genetic testing, we developed a strategy that accounts for the complexity of race and leverages electronic health records for algorithm variables and deploying point‐of‐care dose recommendations.